2006
DOI: 10.1038/sj.sc.3101929
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of lower extremity functional electrical stimulation in early spinal cord injury: lack of efficacy to prevent bone loss

Abstract: Study design: Controlled, repeat-measures study. Objectives: To determine if functional electrical stimulation (FES) can affect bone atrophy in early spinal cord injury (SCI), and the safety, tolerance and feasibility of this modality in bone loss remediation. Setting: Spinal Injuries Units, Royal Adelaide Hospital and Hampstead Rehabilitation Centre, South Australia. Methods: Patients with acute SCI (ASIA A-D) were allocated to FES (n ¼ 23, 2879 years, C4-T10, 13 Tetra) and control groups (CON, n ¼ 10, 31711 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 48 publications
1
31
1
1
Order By: Relevance
“…Hjeltnes et al (1997) also found no increase in bone mineral density as a result of 8 weeks of FES cycling in SCI persons, despite a small increase in total body muscle mass. Similarly, no changes in bone mineral density were reported following FES cycling 3 days per week for 6 months (Leeds et al, 1990) or 5 days per week for 5 months (Clark et al, 2007). Increases in bone density have been reported following FES cycling training 5 days per week for 6 months (Belanger et al, 2000) and 3 days per week for 12 months (Mohr et al, 1997).…”
Section: Bonementioning
confidence: 91%
“…Hjeltnes et al (1997) also found no increase in bone mineral density as a result of 8 weeks of FES cycling in SCI persons, despite a small increase in total body muscle mass. Similarly, no changes in bone mineral density were reported following FES cycling 3 days per week for 6 months (Leeds et al, 1990) or 5 days per week for 5 months (Clark et al, 2007). Increases in bone density have been reported following FES cycling training 5 days per week for 6 months (Belanger et al, 2000) and 3 days per week for 12 months (Mohr et al, 1997).…”
Section: Bonementioning
confidence: 91%
“…Previous literature has shown that the knee-joint torques during FES-LCE cycling may be great enough to produce a fracture in the compromised lower limbs of an individual with SCI, 8 and others have been equally conservative in their exclusion of participants due to a history of bone fracture and/or osteoporosis. 8,10,15 …”
Section: General Eligibility Criteriamentioning
confidence: 98%
“…There is a suggestion of a dose-dependent effect, 70 and the effects disappear if cycling is not sustained. 71 The results of two studies investigating the effects of electrical stimulation applied to the quadriceps with the participant in supine during the first few weeks after injury have yielded different results with respect to prevention of bone loss in the femur. 72,73 Contradictory effects have also been reported for standing training, possibly related to differences in dosage.…”
Section: Exercise and Bonementioning
confidence: 99%